PENERAPAN MODEL PEMBELAJARAN TTW (THINK-TALK-WRITE) UNTUK MENINGKATKAN KOMPETENSI SISWA MENULIS TEKS DESKRIPTIF - Hastutik, Wiji (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2022)
The students’competency achievement is the main goal of teaching learning process, but It’s not easy as we think. In fact there are many students face learning loss. It really happened in SMP Negeri 2 Muara Bungo in writing simple desciptif text. This research is intended for describing the applying of TTW (Think-Talk-Write) learning model to improve the competency. It is included in classroom action research that involved 32 students of class VII.A as the research sebject. This research consist of two cycles. Each of them has four phases . They are planning, doing, observing and reflecting. The instrument in data collecting used observation sheet, test and field note. At the end of the research showed that (1)The applying of TTW (Think-Talk-Write) learning model are able to increase the students’ competency in writing descriptive text. It is showed from the test result that there was15.7%in developing the idea (content)from the first cycle to the second, increasing 6.3 % in advancing the vocabulary from the first cycle to the second, increasing 9.3% in using the grammar, and increasing 6,3% in the aspect of coherence of the sentences. (2) The applying of TTW (Think-Talk-Write) learning model also improve the students’ motivation in learning English.